Question

Let G be group If H is a subgroup of G, show that for all g∈G the set g*H*g^(-1)={g*H*g^(-1) ├|h∈H┤} is a subgroup of G Show that if H is finite, then g*H*g^(-1) is also finite and has the same number of elements as H.

230

likes1151 views

Fred

4.4

110 Answers

1. **Mostrar que $gHg^{-1}$ es un subgrupo de $G$:**

- **Cerradura:** Para $a, b \in gHg^{-1}$, $a = gh_1g^{-1}$ y $b = gh_2g^{-1}$, donde $h_1, h_2 \in H$. Entonces,ab = (gh_1g^{-1})(gh_2g^{-1}) = gh_1(h_2g^{-1}) = g(h_1h_2)g^{-1}.

Como $H$ es subgrupo, $h_1h_2 \in H$, entonces $ab \in gHg^{-1}$.

- **Identidad:** Como $e \in H$ (elemento identidad de $H$) y $ge(g^{-1}) = g g^{-1} = e \in gHg^{-1}$, la identidad de $G$ también está en $gHg^{-1}$.

- **Inverso:** Para $a \in gHg^{-1}$, $a = ghg^{-1}$, donde $h \in H$. El inverso de $a$ esa^{-1} = (ghg^{-1})^{-1} = g^{-1}(h^{-1})g.

Como $h \in H$ implica $h^{-1} \in H$, entonces $a^{-1} = g(h^{-1})g^{-1} \in gHg^{-1}$.

2. **Mostrar que $\#(gHg^{-1}) = \#H$ si $H$ es finito:**

- Dado que la función $f: H \to gHg^{-1}$ tal que $f(h) = ghg^{-1}$ es un bijectivo, el conjunto $gHg^{-1}$ tiene la misma cardinalidad que $H$.

Entonces, $gHg^{-1}$ es un subgrupo de $G$. Y además, si $H$ es finito, $gHg^{-1}$ es finito y tiene el mismo número de elementos que $H$. Así, $\#(gHg^{-1}) = \#H$.

- **Cerradura:** Para $a, b \in gHg^{-1}$, $a = gh_1g^{-1}$ y $b = gh_2g^{-1}$, donde $h_1, h_2 \in H$. Entonces,

Como $H$ es subgrupo, $h_1h_2 \in H$, entonces $ab \in gHg^{-1}$.

- **Identidad:** Como $e \in H$ (elemento identidad de $H$) y $ge(g^{-1}) = g g^{-1} = e \in gHg^{-1}$, la identidad de $G$ también está en $gHg^{-1}$.

- **Inverso:** Para $a \in gHg^{-1}$, $a = ghg^{-1}$, donde $h \in H$. El inverso de $a$ es

Como $h \in H$ implica $h^{-1} \in H$, entonces $a^{-1} = g(h^{-1})g^{-1} \in gHg^{-1}$.

2. **Mostrar que $\#(gHg^{-1}) = \#H$ si $H$ es finito:**

- Dado que la función $f: H \to gHg^{-1}$ tal que $f(h) = ghg^{-1}$ es un bijectivo, el conjunto $gHg^{-1}$ tiene la misma cardinalidad que $H$.

Entonces, $gHg^{-1}$ es un subgrupo de $G$. Y además, si $H$ es finito, $gHg^{-1}$ es finito y tiene el mismo número de elementos que $H$. Así, $\#(gHg^{-1}) = \#H$.

Frequently asked questions (FAQs)

What is the period of the trigonometric function f(x) = 3sin(4x) + 2cos(5x)?

+

What is the equation of a graph that forms a straight line when plotted on Cartesian coordinates?

+

Math question: What is the slope of the line represented by the equation y = 3x + 2?

+

New questions in Mathematics